PENGARUH FAKTOR-FAKTOR PAPARAN BISING MESIN PESAWAT TERBANG TERHADAP GANGGUAN KEMAMPUAN PENDENGARAN PADA KARYAWAN YANG BEKERJA DI APRON BANDARA SUPADIO PONTIANAK PADA BULAN JANUARI 2011 - ., Alrahman Joneri (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Noise is unwelcome, often destructive and a source ofdanger in the workplace. There is a significant increase of noise in theworkplace such as the airport. Supadio airport is the largest airport locatedin West Kalimantan.Objective. This research aims to determine the influence of noiseintensity, time of exposure, tenure, and the use of ear protective devicesfor hearing loss from noise exposure.Method. This research was descriptive analytic using with cross-sectionalapproach. The research was conducted to measure the noise intensity,anamnesis, physical examination and hearing examination for employees.Results. This research found the highest noise in the Supadio AirportsApron was 86 dB and there are 28 employees (46%) from 60 employeeshad hearing impairements from noise exposure. Statistical tests showedthat the noise intensity have a significant influence (p <0.05, time ofexposure had no significant influence (p> 0.05), tenure has no significantinfluence (p> 0.05), and the use of ear protective devices does not have asignificant influence (p> 0.05) for hearing impairements.Conclusion. There is a significant influence between the noise intensitywith hearing impairements from noise exposure, but there were nosignificant influence between the time of exposure, tenure and the use ofear protective devices with hearing impairements from noise exposure.Keyword: hearing impairements, noise, airport 1) Medical School, Faculty of Medicine, Tanjungpura University,Pontianak, West Kalimantan.2) Department of Community Medicine, Faculty of Medicine,Tanjungpura University, Pontianak, West Kalimantan.3) Department of Parasitology, Faculty of Medicine, TanjungpuraUniversity, Pontianak, West Kalimantan.